Cervical cancer and blood group. - Valdivia, Eduardo (2015)
The analysis presented on 2,151 patients with cervical cancer and blood group, it is not positive to support him any correlation. The figures show almost a similar distribution to the one with the rest of the "normal population", and exactly superimposed with the statistics reported by Dr. Velasco in 8,610 women who have another disease but not cervical cancer.